Sharing the Fame but Taking the Blame: When Declaring a Single Person Responsible Sovles a Free Rider Problem - Xinyu Li; Wendelin Schnedler (ZBW - Leibniz Information Centre for Economics, 2024)
Teams are formed because input from different people is needed. Providing incentives to team members, however, can be difficult. According to received wisdom, declaring all members responsible fails because real responsibility for team output "diffuses." But why? And why and when does formally declaring one member "responsible" mean that this member can be attributed "real" responsibility? We offer a model that answers these questions. We identify when jointly declaring a team responsible results in reputation free-riding. We show that declaring one person responsible can overcome this problem but only if all other team members are protected from being sanctioned.
Keywords: M54; D23; D86; L23; K12; K13; 650; reputation free riding; collective punishment; formal and real responsibility